Differences in clinical features and dengue severity between local and migrant Chinese with dengue infection in Singapore - Xu, Chuanhui (2018)
Dengue is endemic in Singapore but not China. We compared clinical features and disease severity of dengue between local and migrant Chinese, most of whom were construction workers, in Singapore. A retrospective study with all hospitalized dengue patients from 2005 to 2008 were performed, including 2609 local and 1195 migrant Chinese. Compared with local Chinese, migrant Chinese were younger. There were more males, but fewer had comorbidities. Migrant Chinese had more headache, eye pain, nausea and myalgia. They had significantly lower median leukocyte count, ALT and AST, and higher platelet count nadir. Among warning signs, migrant Chinese had significantly less persistent vomiting, clinical fluid accumulation, hepatomegaly, hematocrit rise with rapid platelet drop, and more mucosal bleeding. Adjusted for age, gender and comorbidities, migrant Chinese were significantly at higher risk of dengue hemorrhagic fever (DHF) (adjusted odds ratio [aOR]: 1.20, 95% confidence interval [CI]: 1.03–1.41) and dengue shock syndrome (aOR: 1.49, 95% CI: 1.06–2.10), and had longer hospitalization (β coefficient value: 0.27, 95%CI: 0.09–0.44, p = 0.003). There was 1 death among migrant Chinese and 2 deaths among local Chinese. We documented differences in clinical and laboratory features, and dengue severity between local and migrant Chinese in Singapore. Migrant Chinese may need more medical attention given higher risk of DHF.